2013
DOI: 10.1111/jace.12675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyrolysis Temperature on Sol–Gel Synthesis of Lead‐free Piezoelectric (K,Na)NbO3 Films on Nb:SrTiO3 Substrates

Abstract: Lead-free (K,Na)NbO 3 (KNN) piezoelectric films were fabricated on Nb:SrTiO 3 substrates by sol-gel process, and the influence of thermal processing details on the microstructure and ferroelectric property was investigated. Experimental results confirmed the different appearance of polycrystalline growth and epitaxial growth modes during the crystallization of KNN thin films. These two growth modes occurred under different thermal conditions within the narrow pyrolysis temperature scope ranging from 400°C to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…5(b). However, a previous study revealed an accompanying growth mode of the [101] preferred orientation in [110]-oriented films 16. For this [101] growth, the [101] polarization dipole is parallel to the film normal direction (also the test direction).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…5(b). However, a previous study revealed an accompanying growth mode of the [101] preferred orientation in [110]-oriented films 16. For this [101] growth, the [101] polarization dipole is parallel to the film normal direction (also the test direction).…”
mentioning
confidence: 96%
“…11 However, more detailed studies are needed to investigate the precise crystallographic structure of KNN films on cubic substrates because of the lattice parameter differences existing between KNN and PZT systems. 14, 15 We fabricated KNN-based films by sol-gel processing, whose details can be found elsewhere, 8,16 The sol solution was prepared from sodium ethoxide [NaOC 2 H 5 ] (>99%), potassium ethoxide [KOC 2 H 5 ] (>98%), niobium pentaethoxide [Nb(OC 2 H 5 ) 5 ] (>99.999%), and manganese acetate [Mn(CH 3 COO) 2 ] (>98%), which was dissolved in 2-methoxyethanol (>99.0%) with acetic acid (>99.5%), acetylacetone (>99.0%), and formamide (>99.0%) as stabilizer, chelating agent, and drying controller, respectively. The compositions of the solution were adjusted to (K 0.5 Na 0.5 )NbO 3 with 10% alkali-metals excess and 2% Mn-doping to reduce leakage current without changing phase structure.…”
mentioning
confidence: 99%
“…This incorporation would create ionic compensation between Nb 5+ and Y 3+ at the B-site and reduce the interaction of octahedron molecules (Nb 5+ and O 2-) as a result. Due to weak octahedron interaction, the oxygen rapidly vaporizes and induces the oxygen vacancies in the KNN lattice 24 . Following that, the oxygen vacancies promote the localized defects in KNN lattices which cause the conductivity to be reduced remarkably.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…As can be observed, the KNN films obtained with low excess amount of alkaline metals, 0 mol% (50/50) and 10 mol% (60/60), show a higher degree of misorientation with the presence of other reflexions different to those of {100} orientation associated to the formation of the secondary phase. It is known that the pyrolysis temperature is a critical processing condition parameter for preferential orientation [13,21]. In our study, all the films were prepared under the same pyrolysis conditions and only the excess amount of Na and K was changed.…”
Section: Figure 2 Xrd Patterns Of Knn (A) and Knn-la (B) Thin Films mentioning
confidence: 99%
“…Although textured films can been obtained using SrTiO 3 (STO) substrates [13], the main problems concerning KNN-based thin films are the low stability of the precursor solutions, the low control of stoichiometry and the difficulty in achieving epitaxial films.…”
Section: Introductionmentioning
confidence: 99%